Macrophages of the subcutaneous and omental fatty tissue in obese patients: Immunohistochemical phenotyping of M2 subtypes in relation to type 2 diabetes - Chyliková, Jaroslava; Dvořáčková, Jana; Čížková, Kateřina; Lacey, Helena; Kamarád, Vojtěch (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2020)
BACKGROUND AND AIMS: Macrophages are linked to the initiation of the chronic inflammation believed to underlie the changes taking place in the white fatty tissue of obese people. Both the number of macrophages, but their functional status, play an important role in the development of inflammation. Classically, macrophages are divided into two types: pro-inflammatory (M1) and anti-inflammatory (M2) types, and based on current immunological studies, further views on the functional distribution of macrophages are suggested. In this study, we evaluated the M1 and M2 macrophages ratio in obese subjects with, or without diabetes. To identify all macrophages, we used CD68 expression, while CD204 expression is typically used for the M2 macrophage. MATERIALS AND METHODS: During bariatric surgery, carried out in obese people with and without type 2 diabetes (T2D), we obtained subcutaneous adipose tissue from the navel and omental adipose tissue. We also obtained the same tissue from people with a physiological range of BMI from a judicial autopsy. Applying immunohistochemical staining anti-CD68 and anti-CD204, we carried out a quantitative evaluation of the number of macrophages. RESULTS: We found CD68+ and CD204+ positive macrophages in perivascular spaces and between fat cells, both isolated and in larger infiltrates. They were also present in so-called "crown-like structures" (CLS) around dying adipocytes. Quantitative analysis showed an increased number of macrophages in all obese patients compared to the control group of non-obese, individuals without T2D. The most striking observation was the macrophage increase in the visceral fatty tissue of diabetics. The number of CD68 and CD204 positive macrophages was statistically significantly smaller in patients without T2D. CONCLUSION: We demonstrated a significantly greater number of macrophages in visceral adipose tissue, especially in patients with T2D. Our results also show a positive correlation between the presence of T2D and the total number of macrophages; a significantly greater number of macrophages were found in visceral adipose tissue, especially in patients with T2D.
Keywords: Antigens, CD; obezita; Bariatric Surgery; omentum; CD antigeny; Humans; Case-Control Studies; lidé středního věku; studie případů a kontrol; Adipose Tissue, White; Intra-Abdominal Fat; Female; Aged; makrofágy; dospělí; imunofenotypizace; mladý dospělý; senioři; lidé; Immunohistochemistry; imunohistochemie; Diabetes Mellitus, Type 2; Adult; Subcutaneous Fat; Immunophenotyping; Omentum; ženské pohlaví; nitrobřišní tuk; Scavenger Receptors, Class A; Male; Middle Aged; bariatrická chirurgie; Young Adult; scavengerové receptory - třída A; bílá tuková tkáň; antigeny diferenciační myelomonocytární; Obesity; Macrophages; mužské pohlaví; diabetes mellitus 2. typu; Antigens, Differentiation, Myelomonocytic; podkožní tuk